Microbial flora of the trachea during intubation of patients undergoing upper abdominal surgery. Issue 10 (October 1992) - Dilworth, J P; White, R J; Brown, E M
Abstract : BACKGROUND: The presence of Haemophilus influenzae in the oropharynx is correlated with the subsequent development of chest infection. The importance of colonisation of the trachea by bacteria at the time of surgery is uncertain. This study investigated the tracheal flora at the time of intubation in 24 patients undergoing elective upper abdominal surgery. METHODS: The bacterial flora of the trachea was sampled in all 24 patients immediately after intubation and immediately before extubation. Patients were assessed postoperatively for the development of chest infection. RESULTS: Bacteria, including H influenzae in five cases, were isolated from the post-intubation brushings of the trachea of 15 patients. The pre-extubation brushings from only four patients yielded growth. Three of five patients developing a chest infection were colonised by H influenzae according to the postintubation brush, compared with two of 19 without chest infections. Before extubation two of five developing chest infections had H influenzae in the trachea but none of 19 without infection. All but one of the patients from whom H influenzae was isolated were smokers. CONCLUSIONS: These results suggest that the increased risk of postoperative chest infection in cigarette smokers may be due in part to colonisation of the trachea by H influenzae at the time of operation.